LEGAL LIABILITY OF THE PARTIES TO THE TRAGEDY OF THE MATCH AT KANJURUHAN STADIUM INDONESIA - Rianda Dirkareshza; M. Rizki Yudha Prawira (Syiah Kuala Law Journal, 2022)
Fanaticism towards high football in Indonesia has essentially been embedded in people's lives. The adverse impact of the phenomenon on his travels has evolved into hooliganism. The purpose of this article is to find out the responsibility of the parties to the tragedy of the match at the Kanjuruhan Stadium in Indonesia. The research methods used are Normative Juridical and Socio Phenomena to reveal cases that do not yet have permanent legal force (In Kracht) so that they are classified into a phenomenon, the approaches used are Statue Approach and the case approach. The results of the study revealed first, the organizing committee violated the provisions of Article 19 letter b of the FIFA Legal Handbook which states "firearms or mass control gas must not be carried or used and Article 21 letter c the organizing committee is required to ensure that no door or gate is locked under any circumstances. Second, the Executive Committee of the Police element is indicated to have violated the Regulation of the Chief of Police of the Republic of Indonesia Number 1 of 2009 concerning the Use of Force in Police Actions which regulates the stages that must be carried out when wanting to use force. Third, the Indonesian Football Association (PSSI) is assumed to be responsible in accordance with 50 paragraphs (1) of Law Number 11 of 2022 concerning Sports.